Current Good Manufacturing Practice Production of an Oncolytic Recombinant Vesicular Stomatitis Viral Vector for Cancer Treatment - Ausubel, L.J. (Mary Ann Liebert, Inc., 2011)
Vesicular stomatitis virus (VSV) is an oncolytic virus currently being investigated as a promising tool to treat cancer because of its ability to selectively replicate in cancer cells. To enhance the oncolytic property of the nonpathologic laboratory strain of VSV, we generated a recombinant vector [rVSV(MΔ51)-M3] expressing murine gammaherpesvirus M3, a secreted viral chemokine-binding protein that binds to a broad range of mammalian chemokines with high affinity. As previously reported, when rVSV(MΔ51)-M3 was used in an orthotopic model of hepatocellular carcinoma (HCC) in rats, it suppressed inflammatory cell migration to the virus-infected tumor site, which allowed for enhanced intratumoral virus replication leading to increased tumor necrosis and substantially prolonged survival. These encouraging results led to the development of this vector for clinical translation in patients with HCC. However, a scalable current Good Manufacturing Practice (cGMP)-compliant manufacturing process has not been described for this vector. To produce the quantities of high-titer virus required for clinical trials, a process that is amenable to GMP manufacturing and scale-up was developed. We describe here a large-scale (50-liter) vector production process capable of achieving crude titers on the order of 10(9) plaque-forming units (PFU)/ml under cGMP. This process was used to generate a master virus seed stock and a clinical lot of the clinical trial agent under cGMP with an infectious viral titer of approximately 2 × 10(10) PFU/ml (total yield, 1 × 10(13) PFU). The lot has passed all U.S. Food and Drug Administration-mandated release testing and will be used in a phase 1 clinical translational trial in patients with advanced HCC.